A6.16 Harmonisation of eleven flow cytometers for multi-colour analyses of a large cohort of patients in the context of the european imi project "precisesads". (24th February 2016) - Pers, JO; Lann, L Le; Marañon, C; Barbarroja, N; Alvarez, D; Trombetta, E; Gerl, V; Zuber, A; Cantaert, T; Neves, E; Kniesch, K; Ducreux, J; et al.
Abstract : Background and objectives: The "Molecular Reclassification to Find Clinically Useful Biomarkers for Systemic Autoimmune Diseases" (PRECISESADS) IMI project will study 2, 500 individuals affected by SADs into clusters of molecular, instead of clinical entities. Among extensive OMICS approaches, patients will get flow cytometry analyses using 9 panels of Abs, containing 8 different multi-stained markers, that will be performed in 11 various centres equipped with different flow cytometers (Canto II, Aria III, Fortessa, Verse, Navios or Gallios). The aim of this work was to establish a method to harmonised all the cytometers to be able to compared the overall data. Materials and methods: VersaComp capture beads (Beckman Coulter) were used for the mirroring of the 11 flow cytometers. Rainbow 8 - peak beads (Beckman Coulter) were used to settle internal quality control for each machine. Duraclone tubes (Beckman Coulter) containing dried Ab cocktail were used for the multi-colour staining of the blood samples. Results: A Navios has been chosen as the internal reference to fix the MFIs of the 8 different fluorochrome-conjugated Abs (FITC, PE, PC5.5, PC7, APC, APC-AF750, PB and KrO) using the VersaComp Ab capture beads. The 10 other centres have then fixed their own PMT values to reach the same MFIs using the same conjugated Abs. Thereafter, each centre acquired the Rainbow 8 - peak beads to determine their own internal QC. One blood sample has been dispatched in all centres and has been concomitantly stained with the Duraclone tubes (Beckman Coulter) . Frequencies of cell subsets and MFIs of markers have been compared and found similar between centres. Conclusions: The prerequisite of the integration of the flow cytometry informations in bioinformatical and biostatistical analyses of the OMICS data is a fine inter-cytometer harmonisation. This procedure has been succesfully achieved getting a very close sensitivity for all flow cytometers. The inclusion of patients can now be confidently performed, knowing that the comparison of the flow cytometry data will be workable. Identification of specific molecular signatures in patients with SADs should finally enable clinicians to tailor individual therapies. (This work has received support from EU/EFPIA Innovative Medicines Initiative Joint Undertaking PRECISESADS grant n°115565).